ChemInform Abstract: Synthesis and Antiproliferative Efficiency of Novel Bis(imidazol‐1‐yl)vinyl‐1, 2, 4‐oxadiazoles. Issue 29 (29th June 2016) - Nandeesh, Kebballi N.; Swarup, Hassan A.; Sandhya, Nagarakere C.; Mohan, Chakrabhavi D.; Pavan Kumar, Chottanahalli S.; Kumara, Manikyanahalli N.; Mantelingu, Kempegowda; Ananda, Sannaiah; Rangappa, Kanchugarakoppal S.
Abstract: The title oxadiazoles are efficiently synthesized by a one‐pot reaction between N, N′‐carbonyldiimidazole, trifluoropropionic acid and various amidoximes.